Effects of acute application of mucoadhesive buccal films with propranolol hydrochloride in an animal model of essential hypertension - Kurćubić, Ivana; Vajić, Una-Jovana; Cvijić, Sandra; Crevar, Milkica; Ibrić, Svetlana; Miloradović, Zoran; Mihailović-Stanojević, Nevena; Ivanov, Milan; Karanović, Danijela; Jovović, Djurdjica; Djuriš, Jelena (Archives of Pharmacy, 2022)
Mucoadhesive buccal films can improve drug absorption by prolonging its retention time on the buccal mucosa. The aim of the study was a comparative assessment of the hemodynamic effects and pharmacokinetics of propranolol hydrochloride (PROP) after buccal and oral administration in spontaneously hypertensive rats. Animals were divided into 3 groups: Group I (control) received 0.5 mL of water with a gastric tube, group II received an immediate-release 10 mg PROP tablet via gastric tube, and group III received a mucoadhesive 10 mg PROP buccal film. Systolic (SP) and diastolic blood pressure (DP), and heart rate (SF) were measured in rats, and pharmacokinetic PROP parameters, Cmax, tmax, and AUC0 → 24, were calculated by noncompartmental analysis. Mucoadhesive buccal films showed superior degree of absorption of PROP over immediate-release tablets (AUC0 → 24: 69.64 µgh/ml versus 24.61 µgh/ml). The tmax value was significantly higher in mucoadhesive buccal films, which indicates a prolonged PROP release and longer therapeutic effect (71.19h versus 29.73h). There was no statistically significant difference in Cmax values ​​between groups II and III of rats (4.74 µg ml versus 7.11 µg ml). Mucoadhesive buccal films provide a more pronounced and long-lasting reduction primarily of SF (reduction of 28-51% lasting from 10 minutes to the twelfth hour of testing), but also SP and DP (between 15-30% from the first to the sixth hour of testing) compared to immediate-release tablets. Mucoadhesive buccal films allow bypass/reduction of the extensive hepatic first-pass metabolism, and consequently improve the therapeutic PROP effect.